Is Herbal Mouthwash as Effective as Chlorhexidine?: A Review - Sheila Soesanto; Jessica Endriyana; Priska Natassya (Faculty of Dentistry, Universitas Trisakti, 2023)
Pathogenic biofilms contribute to several oral problems, including caries, periodontitis, and other infections. Chlorhexidine has long been considered the gold standard for chemical dental plaque control. However, it is accompanied by adverse effects, such as taste alterations, staining, and cytotoxicity. In response to these challenges, herbal mouthwashes have emerged as a promising alternative treatment, with fewer drawbacks. The primary aim of this review was to assess the effectiveness of herbal mouthwashes in comparison to chlorhexidine. Adhering to the PRISMA guidelines, this review focused on questions concerning the effectiveness of herbal mouthwashes compared to chlorhexidine. A systematic search was executed in prominent databases, including PubMed, SpringerLink, ScienceDirect, and Wiley. Using predefined keywords, five articles were selected for inclusion in the review and subsequent research synthesis. The review findings suggest that herbal mouthwashes exhibit effectiveness comparable to chlorhexidine, accompanied by the added benefit of fewer side effects. However, further research is needed to comprehensively evaluate the long-term safety and efficacy of herbal mouthwash.